Hilbert transform of a wavelet system: boundedness of orthogonal projections in the uniform norm - G. G. Gevorkyan; A. Kamont (Հայաստանի ԳԱԱ)
Let ψ be a wavelet associated with a scaling function φ, and let ~ ψ be the Hilbert transform of ψ. Under some natural conditions on the smoothness and decay of φ, we show that the orthogonal projections onto the spaces generated by ~ ψ are bounded in the uniform norm.
Keywords: Mathematics; Science; General Works